The Epigenetic Effects of Coffee - Qi Ding; Yan-Ming Xu; Andy T. Y. Lau (Molecules, 2023)
In this review, we discuss the recent knowledge regarding the epigenetic effects of coffee extract and the three essential active ingredients in coffee (caffeine, chlorogenic acid, and caffeic acid). As a popular beverage, coffee has many active ingredients which have a variety of biological functions such as insulin sensitization, improvement of sugar metabolism, antidiabetic properties, and liver protection. However, recent researches have shown that coffee is not only beneficial for human, but also bad, which may be due to its complex components. Studies suggest that coffee extract and its components can potentially impact gene expression via alteration of DNA methylation, histone modifications, and ncRNA expression; thus, exert long lasting impacts on the epigenome. More importantly, coffee consumption during pregnancy has been linked to multiple negative effects on offspring due to epigenetic modifications; on the other hand, it has also been linked to improvements in many diseases, including cancer. Therefore, understanding more about the epigenetic effects associated with coffee components is crucial to finding ways for improving human health.